Developing Students' God-Conscious Character through FASTI-Based Islamic Entrepreneurship - Yully Trisnaningtyas; Vera Yuli Erviana; Muhammad Zuhaery (CV. Media Digital Publikasi Indonesia, 2026)
The implementation of entrepreneurship education in Islamic schools aims not only to develop entrepreneurial competencies but also to foster students' God-conscious character through the enactment of Islamic values. However, previous studies have paid limited attention to the implementation of Islamic entrepreneurship that integrates FASTI values as a mechanism for developing God-conscious character in Islamic schools. This study aims to analyze the implementation of Islamic entrepreneurship in fostering students' God-conscious character at SMPIT Istiqamah Balikpapan by employing the POAC (Planning, Organizing, Actuating, and Controlling) management functions as the analytical framework for program implementation. A qualitative case study approach was adopted. Participants were purposively selected and included the principal, the vice principal for curriculum affairs, and teachers responsible for implementing the Islamic entrepreneurship program. Data were collected through interviews, observations, and document analysis and were analyzed using the Miles and Huberman interactive model with the support of qualitative data analysis software. The findings reveal that the implementation of Islamic entrepreneurship through project-based learning facilitates the enactment of FASTI values, thereby contributing to the development of students' God-conscious character. This character is reflected in enhanced religious awareness, honesty, responsibility, respectful communication, the application of Islamic business ethics, and social responsibility. The study proposes an implementation model of Islamic entrepreneurship that integrates project-based learning and the enactment of FASTI values as a conceptual framework for fostering God-conscious character in Islamic schools.